Refining and expanding global climate change scenarios in the sea: Poleward creep complexities, range termini, and setbacks and surges. Issue 5 (21st March 2017) - Canning‐Clode, João; Carlton, James T.
Abstract: Aim: Invasion dynamics are sensitive to global‐scale changes. New marine invasions have been recorded in dramatically increasing numbers along the world's coasts, due, in part, to the global warming of the oceans and the ability of many successful invasive marine species to tolerate a broader thermal range than native species. As a response to ocean warming, a poleward movement of numerous species has been observed in many biogeographic regions. Our aim was to explore several poorly recognized and thus rarely studied aspects of ocean climate change scenarios in order to advance our understanding of finer‐grained aspects of poleward movements. Location: Global. Methods: Three scenarios are investigated in our framework: (1) the existence of networks of complex intraregional origins, routes and destinations of poleward‐moving species, (2) the existence of impenetrable termini where no further expansion is possible, linked to potential outflow corridors, and (3) the interplay of a warming ocean with aperiodic cold episodes. Results: Poleward advances consist of distinct regional networks of origins, routes and destinations, largely undefined in most areas, linked in turn to the potential existence of endpoints where no further expansion may be possible without escape routes and/or human‐mediated assistance. The interaction of aperiodic cooling periods may result in temporary setbacks or rate reductions in range expansions. Main conclusions: The recognition of potentially complex origin‐route‐destination networks may significantly advance our predictive capacity of both future invasions and range expansions and potential impacts. Thus, specific focus on high‐profile donor region species pools linked to established vector routes may yield far more robust management scenarios than currently in place. While it is probable that the frequency of climate‐mediated surges (inevitable warming) and setbacks (cooling periods) of species invasions will increase over time, the net outcome is likely to be positive, resulting in an inexorable poleward expansion of thousands of species.